Field evaluation of tomato varieties/breeding lines against tomato yellow leaf curl virus disease (TYLCV) - Segbefia, M.M.; Amoatey, H.M.; Ahiakpa, J.K.; Quartey, E.K.; Appiah, A.S.; Nunoo, J.; Kusi-Adjei, R. (Pertanika Journal of Tropical Agricultural Science, 2018)
Tomato Yellow Leaf Curl Virus (TYLCV) is currently the most devastating virus of cultivated tomatoes in tropical and subtropical regions, accounting for significant yield losses in cultivated tomato in Ghana. Severe population outbreaks of the whitefly vector (Bemisia tabaci), are usually associated with high incidence of the disease. Resistance breeding is the surest solution to TYLCV in developing viable seeds for increased tomato production in Ghana. The Wild tomato (Solanum pimpinellifolium L.) is a recognised crop Wild species (CWS) with resistance genes to different diseases including the TYLCV disease and possesses good fruit quality traits in Ghana. Three (3) cultivated tomato varieties and seven breeding lines developed from crosses between the Wild tomato and three hybrids, three backcrossed lines and the Wild tomato were evaluated with their parents against TYLCV disease under local field conditions. Field appraisal of whitefly populations, disease incidence and severity, agronomic and yield characteristics of the tomato varieties/breeding lines were undertaken to hasten selection of tolerant/resistant varieties or breeding lines in the breeding programme. Wild tomato (ISSAP = 0.31 and ISSDP = 0.76) and Woso (ISSAP = 1.90 and ISSDP = 2.27) recorded the least and highest average symptom severity on all plants (ISSAP) and diseased plants only (ISSDP); while the least and highest disease incidence was recorded by the Wild tomato (11.10%) and Roma (43.05%). Roma which recorded the highest population of whiteflies in the dry season also exhibited the highest symptom severity on all plants as well as diseased plants during the study period. There was a significant symptom relapse in Wild tomato and Woso x Wild in 6-8 WAT for both ISSAP and ISSDP. Number of fruits per plant, ISSAP and ISSDP were positively and/or inversely correlated (r = 0.98, 0.93, -0.83) with average whitefly count, percent disease incidence and yield (t/ha).
Keywords: Backcross; Geminiviruses; Ghana; Resistance breeding; Tomato; TYLCVD; Varieties/breeding lines